If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(4r-2)+9=-14r+15+2r
We move all terms to the left:
-3(4r-2)+9-(-14r+15+2r)=0
We add all the numbers together, and all the variables
-3(4r-2)-(-12r+15)+9=0
We multiply parentheses
-12r-(-12r+15)+6+9=0
We get rid of parentheses
-12r+12r-15+6+9=0
We add all the numbers together, and all the variables
=0
r=0/1
r=0
| -8−10d=-8d | | y=-6(-1)-3 | | -2=3x+5+2 | | y=-6(-5)-3 | | -4y=-5y−10 | | 10+0.2x=16 | | -5m=-4m+6 | | 2(1-6m)=98 | | -13+8r=-3(r-3) | | n=-9+10n | | 2(1+6k)=86 | | 16=5x+8 | | -3=x+5+5+3x | | 7j=8j+9 | | 8(7+8n)=312 | | x2-2x=8. | | -88=8(-v-6) | | -81=-3(7n-1) | | 2x+4+4=10 | | 8−3b=-4b | | 2x+3+3x+6=9 | | 7+4m+10=15-2m | | 6x+4=-6+3x+16 | | -343=-7(7-6a) | | -5(5-3r)=-85 | | -u−8=5u+10 | | 2x+2+4=-4 | | -4+6c=6+4c | | -232=8(1+5x) | | 6r=5r+9 | | 86=-2(8n-3) | | 5v=6v+2 |